A synthesis of an aircraft approach, landing & overrun - Perumal, Kannan; Mansor, Shuhaimi (Faculty of Mechanical Engineering, 2008)
All conventional aircraft flights start at a point of departure with a take-off and end at the destination with a landing. During this phase, the aircraft is transferred from the airborne state to the ground-borne state and brought to a halt. Although landing an aircraft looks simple but in reality it is difficult to predict the performance during this phase due to its very dynamic nature, a high sensitivity to piloting technique and uncertainties in aerodynamics. As this critical manoeuvre (beside takeoff) takes place in close proximity to the ground, and at a low airspeed (‘dirty’), there is a relatively a high risk to the safety of the aircraft and its occupants. A significant number of incidents and accidents occur during this crucial phase in which the aircraft could not be stopped on the runway during landing-known as overruns. Although it has been a problem for quite a long time, unfortunately, not much has been learned. This paper presents some important and interesting facts regarding runway overruns and the crucial aspects during the penultimate stages of the landing process together with the airworthiness and regulatory requirements.